Needs Analysis of Professional Competence of Islamic Religious Education and Character Education Teachers in Implementing Merdeka Curriculum - Bakti Komalasari (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
The implementation of the Merdeka Curriculum in Indonesia’s Sekolah Penggerak (Driving Schools) necessitates a significant paradigm shift, demanding dynamic professional competence from Islamic Religious Education (PAI) teachers. This study aims to critically analyze the curriculum implementation process and explicitly identify the specific professional competence gaps PAI teachers face in realizing the Pancasila Student Profile. Employing a qualitative case study approach at SDN 02 and SDN 17 Rejang Lebong, comprehensive data were collected through classroom observation, document analysis, and in-depth interviews with school principals and PAI teachers. The results highlight three pivotal findings. First, while the schools successfully completed the mandatory five-stage intervention, the density and rapid delivery of online instructional materials resulted in a fragmented understanding of the curriculum's philosophical core among teachers. Second, although teachers have initiated diagnostic assessments and the Pancasila Student Profile Strengthening Project (P5), they encounter significant technical challenges in designing differentiated instruction and independently creating adaptive teaching modules that suit diverse student needs. Third, the study identifies a crucial, often overlooked need for specific professional development focused not only on digital literacy but also on psychological competence for character building and student-centered pedagogical strategies. The study concludes that standard, one-size-fits-all training is insufficient. Instead, sustainable, mentor-based coaching that integrates technological proficiency with psychological insights is essential to effectively bridge the gap between national policy expectations and the practical reality of classroom instruction.